The Relationship Between Intrinsic, Extrinsic Factors, and Socio Economic Status With the Level of Pneumonia Among Toddlers at Paal V Health Center, Jambi City - Dela Lupita Sari; Rumita Ena Sari; Hubaybah Hubaybah (Malahayati Nursing Journal, 2024)
ABSTRACT Pneumonia is the most significant trigger of infections leading to death in children globally. Every year, an estimated 921,000 children under the age of 5 die due to pneumonia. This study aims to determine the relationship between intrinsic, extrinsic, and socioeconomic factors with the level of pneumonia in toddlers at the Paal V Community Health Center in Jambi City. This study uses an analytical quantitative research method, with a cross-sectional study design. The respondents in this study were 87 toddlers (aged 0-59 months). Data analysis was conducted using chi-square statistical analysis. The research results show the p-value of intrinsic factors, namely age PR 0.447 (p=0.339), gender PR 0.747 (p=0.668), Exclusive Breastfeeding PR 4.474 (p=0.000), low birth weight PR 2.364 (p=0.064), nutritional status PR 5.250 (p=0.000), history of Vitamin A supplementation PR = 3.897 (p=0.002), history of ARI PR 3.687 (p=0.003), history of asthma PR 5.647 (p=0.008), history of tuberculosis TB 2.514 (p=0.033). Extrinsic factors such as household crowding density PR 5.778 (p=0.000), smoking behavior indoors PR 0.763 (p=0.11). Socioeconomic factors such as mother's education PR 3.055 (p=0.025), mother's occupation PR 0.753 (p=0.036), and household income PR 2.703 (p=0.04). There is a relationship between Exclusive Breastfeeding, nutritional status, history of Vitamin A supplementation, history of ARI, history of asthma, history of Tuberculosis, household crowding density, mother's education, mother's occupation, and household income with the level of pneumonia in toddlers in Jambi City in 2023. Meanwhile, there is no relationship between age, gender, history of low birth weight, and indoor smoking behavior with the level of pneumonia in toddlers in Jambi City in 2023. Keywords: Pneumonia, Toddlers, Intrinsic, Extrinsic, Socioeconomic